Crisis - K. M. Ariff (Gerakbudaya Enterprise, 2014)
Under circumstances that will in the future inextricably bind them, Jenn, a Kadazandusun, meets Rizal before leaving Sabah for a city job in Kuala Lumpur. Urged on by an unusual dream, she lives in a village, befriending old Kerry and his persuasive housemaid, Su Ling. Rizal, who works in risk management, is sacked for probing into a loan misappropriation by his employer. The East Asian financial crisis plunges the Malaysian currency and stock market into turmoil. He joins a special-purpose company handling non-performing loans to help the country out of the deepening financial crisis. The contagion is so viral that Jenn decides to leave Rizal with whom she has been developing a relationship, compelling Su Ling to invoke her past in order to save them. Economists have previously published serious attempts to understand the East Asian crisis. Here, the author invites you into a tale of greed, mistakes, sorrow and redemption, bringing home the lessons learned.